Body composition and dietary pattern of Iranian male soccer players, a large national study - Noormohammadpour, P.; Mazaheri, R.; Abarashi, M.; Halabchi, F.; Seif-Barghi, T.; Alizadeh, Z. (Asian Journal of Sports Medicine, 2019)
Background:Body composition and dietary pattern in athletes are important factors in improving performance. The athletes use a wide range of supplements, most of which are not prescribed by specialists.